Editorial: mesalazine to prevent recurrent acute diverticulitis—the final nail in the coffin. Authors' reply. Issue 4 (14th July 2017) - Kruis, W.; Greinwald, R.
Abstract : Linked Content This article is linked to Gracie and Ford et al and Kruis and Greinwald papers. To view these articles visithttps://doi.org/10.1111/apt.14180 andhttps://doi.org/10.1111/apt.14193 .